(3GdfXQjI GdYGeI dJaJjT GdeSGcf ai bGfhf GdGLQGAGJ GdLfGFjI GdchjJi h GdeUQi (B: s (3OQGSI ebGQfI (B/ s - (3ajUd YjGd MehO ThcGf GdYfRis; (3CMeO YhV HdGds; (3YeQ eMeO eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2018)
(3CSJgOa GdeTQY GdeUQi h GdchjJi ef GdfXQjI GdYGeI ai JaJjT GdeSGcf OGNd GdeLJeY(B: (3MeGjI eeGQSI GdCaQGO dMbhbge h MQjGJge HUhQI BefI(B: (3aVdkG Yf MeGjI GdeUdMI GdYGeI(B: (3h jYJHQ Pdc CUOb JYHjQ Yf Gdbje GdJj jDef HgG GdeLJeY ajeG jJYdb HGdMbhb h GdMQjGJ h GdhGLHGJ GdYGeI GdJi cadgG GdOSJhQ h GdbGfhf(B: (3hJYJHQ MQeI GdeScf ef Cge YfGUQ GdMb ai GdMjGI GdNGUI(B: (3aGdgOa efgG JhajQ GdScjfI h GdgOhA h GdGWeFfGf GdTNUi(B: (3h ef Ke aEf cd GYJOGA YdjgG Ch ONhdgG HZjQ bGfhf(B: (3jeKd GYJOGAG Ydi GdMQjI GdTNUjI(B: (3h GdJi caGdJgG abW HacQI GdLRGA GdLfGFi (B((3GdYbGH(B) (3h EfeG jLH MeGjJgG HbhGYO ELQGFjI JSJgOa PGJ GdMeGjI h gi hXjaI GdSdWI GdeefhMI ddbVGA NdGd fXQg GdOYhi GdLfGFjI(B: (3deG dNWhQI JaJjT GdeSGcf ef VQhQI ai LeY GdOdjd GdeGOi Mhd LQjeI hbYJ HGdaYds
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdLfGFi (B2018.s
(3HHdjhLQGajG(B: (3UaMGJ (B346-369.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFj GdebGQfs; (3GdbGfhf GdLfGFjs -- (3GdchjJs; (3GdbGfhf GdLfGFjs -- (3eUQs; (3JaJjT GdeSGcfs; (3bGfhf GdGLQGAGJ GdLfGFjI GdchjJis; (3bGfhf GdGLQGAGJ GdLfGFjI GdeUQis; (3GdehGKjb hGdGJaGbjGJ GdOhdjI dMQeI GdMjGg GdNGUIs; (3GdTQhW GdTcdjI dJaJjT GdeSGcf s; (3GdVeGfGJ GdbGfhfjI dJaJjT GdeSGcf s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs